A silent chemokine receptor regulates steady-state leukocyte homing in vivo - Kornelia Heinzel; Claudia Benz; Conrad C. Bleul (2007)
The location of leukocytes in different microenvironments is intimately connected to their function and, in the case of leukocyte precursors, to the executed differentiation and maturation program. Leukocyte migration within lymphoid organs has been shown to be mediated by constitutively expressed chemokines, but how the bioavailability of these homeostatic chemokines is regulated remains unknown. Here, we report in vivo evidence for the role of a nonsignaling chemokine receptor in the migration of leukocytes under physiological, i.e., noninflammatory, conditions. We have studied the in vivo role of the silent chemokine receptor CCX-CKR1 by both loss- and gain-of-function approaches. CCX-CKR1 binds the constitutively expressed chemokines CC chemokine ligand (CCL)19, CCL21, and CCL25. We find that CCX-CKR1 is involved in the steady-state homing of CD11c(+)MHCII(high) dendritic cells to skin-draining lymph nodes, and it affects the homing of embryonic thymic precursors to the thymic anlage. These observations indicate that the silent chemokine receptor CCX-CKR1, which is exclusively expressed by stroma cells, but not hematopoietic cells themselves, regulates homeostatic leukocyte migration by controlling the availability of chemokines in the extracellular space. This finding adds another level of complexity to our understanding of leukocyte homeostatic migration.